2013
DOI: 10.3182/20130828-3-uk-2039.00076
|View full text |Cite
|
Sign up to set email alerts
|

Testing Bench for Remote Practical Training in Electric Machines

Abstract: Remote labs are emerging as a necessary tool to support practical classes in engineering studies. It is due to the increasing number of students who combine their studies with work. In fact, there are numerous developments in areas such as electronics and automatic. However, there are only a few of them in the area of electrical machines. This paper presents a testing bench for remote practical training in electric machines. The security challenges presented by these experiments are overcome by software within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The remote lab of electric machines is composed of a synchronous generator driven by a DC machine, (Herrera et al 2013). The student can vary the field current of the first device, maintaining constant the speed of rotation.…”
Section: Introductionmentioning
confidence: 99%
“…The remote lab of electric machines is composed of a synchronous generator driven by a DC machine, (Herrera et al 2013). The student can vary the field current of the first device, maintaining constant the speed of rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Work in this direction is ongoing but the speed of measuring devices also depends on the structure of noise-like signals. Thus, in [5], a high-speed method for determining changes in dynamic parameters of electric motors is proposed, which is based on the use of powerful computing devices. However, taking into account the cost of the means of achieving such a result, it can be concluded that there are cheaper and promising solutions since the main problem is not only to detect such changes but also to be able to respond to further changes as soon as possible.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For this reason, Sáenz et al [17] proposed a structure that allows a remote connection with hardware devices by using a clientserver configuration that serves to the client a JavaScript application; leaving the server a task of running the Java part of the virtual and remote lab. A similar solution was deployed in Herrera et al [18]. They made use of a software solution to provide the security of machinery within their remote bench for testing electrical machine based on Easy Java Simulation (EJS) to connect the real hardware to the user interface for controlling (i) the load voltage and frequency when the machine is connected to the load in an islanded way, and (ii) the active and reactive power injected to the net when the machine is directly connected.…”
Section: Securitymentioning
confidence: 99%